Mechanism of prion generation in vitro - Supattapone, Surachai (Henry Stewart Talks, 2008)
Prion propagation in vitro requires PrP plus an incorporated polyanion, PrPC post-translational modifications influence prion formation, Zinc and copper inhibit PrPSc amplification, Update interview: Cofactor molecules and infectious mammalian prions in vitro, Update interview: Cofactor molecules dictate the strain properties of infectious prions, Update interview: PrPC post-translational modifications influence prion formation, Update interview: Fully infectious prions can be made recombinant PrP substrate lacking post-translational modifications, Update interview: Zinc and copper inhibit PrPSc amplification in vitro
Updated at 2020/05/24